Correlation of miR-150, hsa-let-7e, and miR-146a and gene expression of IL-6, IL-8, IP-10, and MIP-1β during dengue virus infection - Sri Masyeni; Kuntaman Kuntaman; Aryati Aryati; Muchlis AU Sofro; Usman Hadi; Gondo Mastutik; Windu Purnomo; Agus Santosa; Benediktus Yohan; R. Tedjo Sasmono; Erni Juwita Nelwan (Narra J, 2021)
Growing evidence suggests that microRNAs (miRNAs) play a pivotal role in viral infection. The objective of this study was to assess the association between the expression of miR-150, hsa-let-7e, and miR-146a on cytokine expression during dengue infection. Dengue virus (DENV) strain SJN-006, a serotype 2 DENV strain of the Cosmopolitan genotype, isolated in Bali, Indonesia, was used to infect peripheral blood mononuclear cells (PBMCs) isolated from healthy individuals. The relative gene expressions of miR-150, hsa-let-7e, and miR-146a as well as the gene expression of cytokines (IL-6, IL-8, IP-10, and MIP-1β) were determined using quantitative real time - polymerase chain reaction (qRT-PCR) at 6, 12 and 24 hours post infection (hpi). Correlations between the microRNAs and cytokines were analyzed by means of causality tests. Our data suggests that miR-150 and hsa-let-7e were significantly higher in infected-PBMCs after 12 hpi compared to the uninfected-PBMCs (p<0.05). The causality tests demonstrated that miR-150 and hsa-let-7e were negatively correlated with IL-8 expression, meanwhile miR-146a was the contrast. DENV infection was negatively and positively correlated with miR-150 and hsa-let-7e, respectively, after 24 hpi. In conclusion, our data demonstrates the vital role of miR-150, hsa-let-7e, and miR-146a in regulating IL-8 expression with possible different pathways.